2022
DOI: 10.1002/jbm4.10636
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Adenosine Monophosphate (cAMP)‐Dependent Phosphodiesterase Inhibition Promotes Bone Anabolism Through CD8+ T Cell Wnt‐10b Production in Mice

Abstract: Cyclic adenosine monophosphate (cAMP)-dependent phosphodiesterase (PDE) inhibitors such as pentoxifylline (PTX) suppress cAMP degradation and promote cAMP-dependent signal transduction. PDE inhibitors increase bone formation and bone mass in preclinical models and are used clinically to treat psoriatic arthritis by targeting inflammatory mediators including activated T cells. T cell activation requires two signals: antigen-dependent CD3-activation, which stimulates cAMP production; and CD28 co-stimulation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Chen et al (2022) showed that high expression of the histone lysine methyltransferase NSD1 (nuclear receptor binding SET domain-containing protein 1) could predict the overall survival of breast cancer patients, although the subtype of breast cancer that was analyzed was not discussed. Then, they investigated the role of NSD1 in paclitaxel-mediated drug resistance using parental MCF-7 (ER + breast cancer) versus MCF-7 PR (paclitaxel-resistant) cell lines.…”
Section: Wnt10b and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2022) showed that high expression of the histone lysine methyltransferase NSD1 (nuclear receptor binding SET domain-containing protein 1) could predict the overall survival of breast cancer patients, although the subtype of breast cancer that was analyzed was not discussed. Then, they investigated the role of NSD1 in paclitaxel-mediated drug resistance using parental MCF-7 (ER + breast cancer) versus MCF-7 PR (paclitaxel-resistant) cell lines.…”
Section: Wnt10b and Cancermentioning
confidence: 99%
“…PTX, which activates cAMP signaling to downstream effectors PKA, had been recognized to increase bone formation, the mechanism of which was unknown. In a preclinical model, Roser-Page et al (2022) used PTX to investigate bone turnover to determine if the mechanism of action was through T cells secreting WNT10B. PTX induced WNT10B production in CD3- and CD28-activated T cells.…”
Section: Wnt10b and The Immune Systemmentioning
confidence: 99%
“…The inhibition of phosphodiesterases PDE2, PDE3 and PDE4 were found to increase osteoblast differentiation in vitro [40]. The administration of the non-specific PDE inhibitor pentoxifylline increased bone mass in mice through production of Wnt10b from CD8+ T cells [41]. Pentoxifylline also increased skeletal angiogenesis and reversed osteopenia in ovariectomized rats [42].…”
Section: Discussionmentioning
confidence: 99%